Intelligent Optimization Algorithm for Employee Performance Appraisal of Internet Companies Based on Time Series Model - Kuang, Huixia (International Conference on Intelligent Computing and Control Systems (Online), 2022)
Therefore, this study adopts the time series decomposition model, by decomposing the time series into seasonal terms and trend terms, and using the original first-order and second-order adaptive coefficient prediction methods for the trend terms and the first-order and second-order autonomic methods of particle swarm optimization. Adaptation coefficient prediction method, an exponential smoothing prediction model based on time series decomposition mode and particle swarm optimization algorithm is proposed., assessment subject, assessment process, etc., purposefully propose optimization countermeasures and algorithms.